Determinants And Impact Of CSR Assurance: Empirical Study In Public Companies In 2016 - Melinda Haryanto, Calvina (Jurnal Akuntansi, 2019)
This study aims to examine the influence of industry type, leverage, operational coverage on CSR Assurance and CSR Assurance impact on firm value. The population of this research is a public company contained in the list of Forbes Global 2000 in 2016. Samples taken in this study as many as 200 samples by using purposive sampling method. The analysis model used in this research is logistic regression model and multiple linear regression model. The results showed that industry type and operational coverage proved to have a significant positive effect on CSR Assurance. However, leverage is not proven to have a significant negative effect on CSR Assurance, but research results show that leverage has a significant positive effect on CSR Assurance. In addition, CSR Assurance proved to have a significant positive effect on company value.